Qauwamun: The Relationship Of Subordinating Women And Victims Of Domestic Violence In Aceh, Indonesia - Longsatia, Salamah (2016)
This paper aims to focus on the conditions of religious factors in embedded domestic violence in Aceh. The discussion intends to explore the concept of Qawwamūn to describe how traditions of matrifocality and Islam contemporarily inform women’s subjectivities, and also analyse the ways Feminist Anthropology scholars. The conclusion of this study is the key condition factor of Women's Lives and Financial Security to the woman in Acehnese context combines with the traditions of matrifocality and the concept of Qawwamun, as the way to negotiating subjectivity of wife to husband in Aceh. However, the concept of Qawwamun is operated through the interaction with the culture of each area, and interpreted within the framework of religion. In the case of Aceh, the author found that basic religious knowledge of Acehnese women is good. Though it is not applied to all the women in Aceh, with a policy of teaching religion is quite good.